Conceptualizing the innovation process towards the "active innovation paradigm"-trends and outlook - Dirk Meissner; Maxim Kotsemir (Journal of Innovation and Entrepreneurship, 2016)
This paper introduces the evolving understanding and conceptualization of innovation process models. We categorize the different approaches to understand and model innovation processes into two types. First, the so-called innovation management approach focuses on the evolution of corporate innovation management strategies in different social and economic environments. The second type is the conceptual approach which analyses the evolution of innovation models themselves as well as the models' theoretical backgrounds and requirements. The focus in this second approach is the advantages and disadvantages of different innovation models in how far they can describe the reality of innovation processes. The paper focuses on the advantages and disadvantages as well as the potential and limitations of the approaches. It also proposes potential future developments of innovation models as well as the analysis of the driving forces that underlie the evolution of innovation models. The article concludes that the predominant open innovation paradigm requires rethinking and further development towards an "active innovation" paradigm.
Keywords: O14; O30; O31; O32; O33; Q55; 650; Active innovation; Innovation models; Innovation process; Generations of innovation models; Process dimension of innovation; Evolution of innovation models; Innovation management